Prognostic value of carbohydrate antigen 19‐9 in patients undergoing resection of biliary tract cancer. Issue 3 (4th January 2017) - Yamashita, S.; Passot, G.; Aloia, T. A.; Chun, Y. S.; Javle, M.; Lee, J. E.; Vauthey, J.‐N.; Conrad, C.
Abstract: Background: The clinical significance of abnormally high levels of carbohydrate antigen (CA) 19‐9 after resection of biliary tract cancer (BTC) is not well established. The aim of this study was to determine the prognostic value of CA19‐9 normalization in patients undergoing resection of BTC with curative intent. Methods: Patients with BTC undergoing resection with curative intent (1996–2015) were divided into those with normal preoperative CA19‐9 level (normal CA19‐9 group), those with an abnormally high preoperative CA19‐9 level (over 37 units/ml) and normal postoperative CA19‐9 level (normalization group), and those with an abnormally high preoperative CA19‐9 level and abnormally high postoperative CA19‐9 level (non‐normalization group). Overall survival (OS) was analysed and predictors of OS were determined. Results: The normal CA19‐9 group (180 patients) and normalization group (74) had better OS than the non‐normalization group (58) (3‐year OS rate 70·4, 73 and 31 per cent respectively; both P < 0·001). The normal CA19‐9 and normalization groups had equivalent OS ( P = 0·880). On multivariable analysis, factors associated with worse OS were lymph node metastases (hazard ratio (HR) 1·78; P = 0·014) and abnormally high postoperative CA19‐9 level (HR 3·16; P < 0·001). In the normalization group, OS did not differ after R0 versus R1 resection (3‐year OS rate 69 versus 62 per cent respectively; P = 0·372); in the non‐normalization group, patients with R1 resection had worse OS (3‐year OS rate 36 and 20 per cent for R0 and R1 respectively; P = 0·032). Conclusion: Non‐normalization of CA19‐9 level after resection of BTC with curative intent was associated with worse OS. R1 resection was associated with a particularly poor prognosis when CA19‐9 levels did not normalize. Abstract : Normalization of CA19‐9 predicts prognosis